Education-related inequalities in cause-specific mortality: first estimates for Australia using individual-level linked census and mortality data. (14th June 2021) - Welsh, Jennifer; Joshy, Grace; Moran, Lauren; Soga, Kay; Law, Hsei-Di; Butler, Danielle; Bishop, Karen; Gourley, Michelle; Eynstone-Hinkins, James; Booth, Heather; Moon, Lynelle; Biddle, Nicholas; et al.
Abstract: Background: Socioeconomic inequalities in mortality are evident in all high-income countries, and ongoing monitoring is recommended using linked census-mortality data. Using such data, we provide the first estimates of education-related inequalities in cause-specific mortality in Australia, suitable for international comparisons. Methods: We used Australian Census (2016) linked to 13 months of Death Registrations (2016–17). We estimated relative rates (RR) and rate differences (RD, per 100 000 person-years), comparing rates in low (no qualifications) and intermediate (secondary school) with high (tertiary) education for individual causes of death (among those aged 25–84 years) and grouped according to preventability (25–74 years), separately by sex and age group, adjusting for age, using negative binomial regression. Results: Among 13.9 M people contributing 14 452 732 person-years, 84 743 deaths occurred. All-cause mortality rates among men and women aged 25–84 years with low education were 2.76 [95% confidence interval (CI): 2.61–2.91] and 2.13 (2.01–2.26) times the rates of those with high education, respectively. We observed inequalities in most causes of death in each age-sex group. Among men aged 25–44 years, relative and absolute inequalities were largest for injuries, e.g. transport accidents [RR = 10.1 (5.4–18.7), RD = 21.2 (14.5–27.9)]). Among those aged 45–64 years, inequalities were greatest for chronic diseases, e.g. lung cancer [men RR = 6.6 (4.9–8.9), RD = 57.7 (49.7–65.8)] and ischaemic heart disease [women RR = 5.8 (3.7–9.1), RD = 20.2 (15.8–24.6)], with similar patterns for people aged 65–84 years. When grouped according to preventability, inequalities were large for causes amenable to behaviour change and medical intervention for all ages and causes amenable to injury prevention among young men. Conclusions: Australian education-related inequalities in mortality are substantial, generally higher than international estimates, and related to preventability. Findings highlight opportunities to reduce them and the potential to improve the health of the population.